Tribological Behaviour Of Palm Oil Mixed With Fly Ash Microparticles As A Bio-Based Lubricant For Manufacturing Processes - Liew, Pay Jun; Tay, Hock Seng; Yap, Ching Yee; Othman, Intan Sharhida; Raja Abdullah, Raja Izamshah (Malaysian Tribology Society (Mytribos), 2021)
In this study, the effect of different concentrations of fly ash microparticles in palm oil bio-based lubricant was investigated on the coefficient of friction, wear scar diameter, and worn surfaces of steel ball. The bio-based lubricants ranging from 0 to 0.14 wt% were prepared by dispersing fly ash microparticles and surfactant Span 85 in the palm oil by using ultrasonication technique. The tribological test was conducted using Four Ball Tribometer based on ASTM D4172-94 standard. The surface morphology was analysed using Scanning Electron Microscopy (JEOL6010PLUS). The results show that the inclusion of fly ash into palm oil could significantly improve the tribological behavior compared to that of pure palm oil. At the optimum fly ash concentration of 0.12 wt%, lowest coefficient of friction, smallest wear scar diameter and smoothest worn surface can be obtained.